2017
DOI: 10.1080/09297049.2017.1365828
|View full text |Cite
|
Sign up to set email alerts
|

Parent reports of children’s working memory, coping, and emotional/behavioral adjustment in pediatric brain tumor patients: A pilot study

Abstract: Neurocognitive problems in childhood survivors of brain tumors are well documented. Further, research has shown that problems in cognitive functioning may be associated with impairment in the use of complex strategies needed to cope with stress, including secondary control coping strategies (e.g., acceptance and cognitive reappraisal) which have been associated with fewer adjustment problems. The present study measured cognitive function, coping strategies, and adjustment in children ages 6-16 years at the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…One of the limitations of this study is associated with CBCL that parents or nurses report about a child's behaviors. Usually, there is a gap in other reports and reality (32). Measuring behavioral problems with more accurate tools may lead to different results.…”
Section: Discussionmentioning
confidence: 99%
“…One of the limitations of this study is associated with CBCL that parents or nurses report about a child's behaviors. Usually, there is a gap in other reports and reality (32). Measuring behavioral problems with more accurate tools may lead to different results.…”
Section: Discussionmentioning
confidence: 99%
“…It may also be related to the EF deficits commonly found in SB ( Brown et al, 2008 ). Strong EF has been found to be associated with more use of secondary control coping in multiple pediatric populations ( Campbell et al, 2009 ; Desjardins et al, 2018 ). Further, another study found that stronger verbal comprehension was related to increased use of secondary control coping in youth with SCD ( Prussien et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…There was a significant level of heterogen ity across the different studies (I 2 = 54%, p < 0.01) and no significant publication bias w identified t (15) = 0.36, p = 0.72, Figure S5a. 2021) [83] reported more than o independent cohort in their study [24,30,36,37,39,40,42,43,[45][46][47]49,[55][56][57][58]60,61,[63][64][65][66][70][71][72][73][74][75]77,83]. (a) Abso-lute risk-attention problems; (b) Absolute risk-emotional; (c) Absolute risk psychosocial problems…”
Section: Absolute Risk-attention Problemsmentioning
confidence: 98%
“…The publication bias was n significant, as revealed by Egger's test t (18) = 0.92, p = 0.369 (Figure S6a). 2021) [83] reported more than one independent cohort in their study [24,30,36,37,39,40,42,43,[45][46][47]49…”
Section: Standard Mean Difference-attention Problemsmentioning
confidence: 99%
See 1 more Smart Citation